Perylene tetracarboxydiimide as an electron acceptor in organic solar cells: A study of charge generation and recombination - Howard, Ian A.; Laquai, Frédéric; Keivanidis, Panagiotis E.; Friend, Richard H.; Greenham, Neil C. (My University, 2009)
We study charge generation and recombination in organic solar cells that utilize perylene tetracarboxydiimide (PDI) as an electron acceptor and a conjugated polymer as an electron donor. PDI is a promising electron acceptor because of its strong red absorption, LUMO well placed to accept electrons from many conjugated polymers, and good electron mobility. However, we find that, when PDI is finely dispersed in a conjugated polymer, the device efficiency is severely limited by very fast bimolecular charge recombination and that, when the blend is made coarser, the device efficiency becomes limited instead by PDI excitons quickly relaxing into stabilized intermolecular states between PDI molecules rather than undergoing charge transfer. The intramolecular PDI states formed are the same as those observed in PDI blended with poly(styrene) and have lower energy and mobility than the exciton. The two loss channels, that is, bimolecular recombination when charge transfer is fast and reduced charge transfer due to intermolecular state formation when charge transport is better, mean that quantum efficiency may always be low in organic solar cells utilizing PDI unless modification of the PDI can suppress the rate of intermolecular state formation without compromising charge- transport properties. Our results are based on detailed, bias-dependent transient-absorption experiments which also reveal the carrier mobility and internal quantum efficiency (as a function of field) directly in the operating organic solar cells.© 2009 American Chemical Society.
Keywords: Excitons; Absorption; Aromatic compounds; Recombination